Performance of TcI/TcVI/TcII Chagas-Flow ATE-IgG2a for universal and genotype-specific serodiagnosis of Trypanosoma cruzi infection. - Glaucia Diniz Alessio; Fernanda Fortes de Araújo; Denise Fonseca Côrtes; Policarpo Ademar Sales Júnior; Daniela Cristina Lima; Matheus de Souza Gomes; Laurence Rodrigues do Amaral; Marcelo Antônio Pascoal Xavier; Andréa Teixeira-Carvalho; Olindo Assis Martins-Filho; Marta de Lana (Public Library of Science (PLoS), 2017)
Distinct Trypanosoma cruzi genotypes have been considered relevant for patient management and therapeutic response of Chagas disease. However, typing strategies for genotype-specific serodiagnosis of Chagas disease are still unavailable and requires standardization for practical application. In this study, an innovative TcI/TcVI/TcII Chagas Flow ATE-IgG2a technique was developed with applicability for universal and genotype-specific diagnosis of T. cruzi infection. For this purpose, the reactivity of serum samples (percentage of positive fluorescent parasites-PPFP) obtained from mice chronically infected with TcI/Colombiana, TcVI/CL or TcII/Y strain as well as non-infected controls were determined using amastigote-AMA, trypomastigote-TRYPO and epimastigote-EPI in parallel batches of TcI, TcVI and TcII target antigens. Data demonstrated that "α-TcII-TRYPO/1:500, cut-off/PPFP = 20%" presented an excellent performance for universal diagnosis of T. cruzi infection (AUC = 1.0, Se and Sp = 100%). The combined set of attributes "α-TcI-TRYPO/1:4,000, cut-off/PPFP = 50%", "α-TcII-AMA/1:1,000, cut-off/PPFP = 40%" and "α-TcVI-EPI/1:1,000, cut-off/PPFP = 45%" showed good performance to segregate infections with TcI/Colombiana, TcVI/CL or TcII/Y strain. Overall, hosts infected with TcI/Colombiana and TcII/Y strains displayed opposite patterns of reactivity with "α-TcI TRYPO" and "α-TcII AMA". Hosts infected with TcVI/CL strain showed a typical interweaved distribution pattern. The method presented a good performance for genotype-specific diagnosis, with global accuracy of 69% when the population/prototype scenario include TcI, TcVI and TcII infections and 94% when comprise only TcI and TcII infections. This study also proposes a receiver operating reactivity panel, providing a feasible tool to classify serum samples from hosts infected with distinct T. cruzi genotypes, supporting the potential of this method for universal and genotype-specific diagnosis of T. cruzi infection.